Difficulties in choosing a biologic disease-modifying anti-rheumatic drug for the treatment of psoriasis and psoriatic arthritis - I. M. Marusenko; N. N. Vezikova; S. N. Kondrichin; N. D. Silvestrov (Научно-практическая ревматология)
The article presents a clinical observation of a patient with severe psoriasis and psoriatic arthritis. Due to insufficient efficacy of systemic therapy of psoriasis biologic disease-modifying therapy was started, but it was associated with difficulties. Development of erythrodermic form of psoriasis was observed during treatment with infliximab and abatacept was successfully used though it is not registered inRussiafor the treatment of psoriasis.